2021
DOI: 10.1088/1742-6596/1788/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Contact Time Adsorption of Rhodamine B, Methyl Orange and Methylene Blue Colours on Langsat Shell with Batch Methods

Abstract: This study aims to determine the uptake capacity of langsat (Lansium domesticum) skin on the adsorption of dyes along with the contact time. Textile dyes are dyes which is harmful for the environment and living things. This textile industry waste can cause a decrease in water quality. When this carcinogenic dye enters the human body, it can lead to cancer. The process of these dyes adsorption use langsat skin samples. The components of langsat skin that can adsorb dyes are triterpenoids, saponins and flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…in 2015, in the previous study, the functional group that was identified was in the form of OH streching which could be read at wavenumbers 3304.6 and 3289.63 cm-1 which came from hydroxyl groups in alcohols and carboxylic acids at wavenumbers ranging from 3600 to 3200 cm-1 in the FTIR spectrum. Then the identification of the C-H Stretching functional group at the wavenumber 2924.74 cm-1 and group of C=O streching from the ester compound group at the wavenumber 1635.02 cm-1 [15] [16]. Litchi peel Adsorbent is used to overcome the contamination of metal ions Cu(II) and Pb (II) in liquid waste.…”
Section: Characterization Of Samplementioning
confidence: 99%
“…in 2015, in the previous study, the functional group that was identified was in the form of OH streching which could be read at wavenumbers 3304.6 and 3289.63 cm-1 which came from hydroxyl groups in alcohols and carboxylic acids at wavenumbers ranging from 3600 to 3200 cm-1 in the FTIR spectrum. Then the identification of the C-H Stretching functional group at the wavenumber 2924.74 cm-1 and group of C=O streching from the ester compound group at the wavenumber 1635.02 cm-1 [15] [16]. Litchi peel Adsorbent is used to overcome the contamination of metal ions Cu(II) and Pb (II) in liquid waste.…”
Section: Characterization Of Samplementioning
confidence: 99%
“…This is because the amount of adsorbed Mn has exceeded the maximum number of Mn that adsorbents have reached saturation. If a lot of adsorbents have saturated the active site on the surface of the adsorbent, further adsorption time will no longer increase the adsorption and even tends to reduce it (Kurniawati et al 2021).…”
Section: Effect Of Contact Timementioning
confidence: 99%
“…In terpenoid compounds, it contains lanceolate acid and lansiolic acid. 7 Activated carbon used as adsorption is very effective in reducing heavy metal contaminants in the environment. Several studies have used activated carbon as an adsorbent, namely activated carbon from the bark of salak on the adsorption of Cu 2+ metal ions using KOH activator with the best adsorption at a dosage variation of 90 mg with a pH of 5.…”
Section: Introductionmentioning
confidence: 99%